Factors influencing side air curtain deployment in rollover motor vehicle accidents. (3rd July 2020) - Ristow, Jacob; Cordeiro, Minal; Boyle, Daniel; Telehowski, Paul; Atkinson, Theresa
Abstract: Objective: Recent changes in FMVSS have led to the utilization of side air curtains to provide occupant retention during rollover events. However, the safety advantage provided by the air curtains relies on the vehicle system's ability to detect the rollover event and deploy the curtains. The purpose of this study is to identify crash and vehicle characteristics in motor vehicle rollovers that influence side air curtain deployment and occupant outcomes. The current study aims to improve the understanding of rollover events and inspire more robust air curtain deployment strategies. Methods: Study data were extracted from rollover cases documented in the NASS-CDS data set from 2011 to 2015. Vehicle model years of 2011 or later with side air curtains installed were examined. The presence of a rollover sensor in each vehicle was determined from vehicle content data available on the Insurance Institute for Highway Safety's crash rating website. The resulting data set contained 14, 003 weighted cases of rollover accidents in which the side air curtain did not deploy (40 raw count) and 23, 178 cases of deployment (80 raw count). Results: Several crash event and vehicle characteristics were similar for the nondeployed and deployed groups, including number of quarter turns, primary location of damage, initiating event for the rollover, and vehicle model year. However, the nondeployed group included significantly more passenger vehicle body types (vs. SUV or truck) and had a significantly lower rate of rollover sensor presence. Presence of a rollover sensor increased the odds air curtain deployment by a factor of 36.5 (95% confidence interval [CI], 5.06–265). Cases in which both side air curtains deployed resulted in a higher frequency of injured occupants (Maximum Abbreviated Injury Scale [MAIS] ≥ 3). However, rollover events resulting in these injuries were also associated with higher rates of impact with another object or vehicle and damage to the roof of the vehicle, suggesting a higher energy event. Conclusions: Nondeployment of the side curtain airbags in rollovers occurred more frequently in vehicles without dedicated rollover sensors, which were most frequently passenger vehicles.